Carbon-based nanocomposites for sensing applications-a review - Davood Peyrow Hedayati; Stefania Termine; Christopher Bascucci; Paul Al Malak; Paolo Bondavalli; Dionisis Semitekolos; Frank Clemens; Costas Charitidis; Robert Böhm (JPhys Materials)
Carbon nanomaterials exhibit unique morphological and physical properties. When used as fillers in various matrices such as polymers, they can provide enhanced electrical, thermal and mechanical characteristics. The emerging field of sensing technologies has witnessed remarkable advancements, resulting from the integration of carbon-based nanocomposites. This paper presents a comprehensive review of the latest a developments in key carbon-based nanocomposite sensors. First, the unique properties of carbon nanomaterials are reviewed covering the full dimensional spectrum, followed by main synthesis routes addressing critical aspects such as morphology, surface functionalization, and doping strategies. Later, the synergistic effects arising from the combination of carbon nanomaterials with other components, such as polymers, are explored in detail, emphasizing the role of percolation levels in the overall sensing performance. The different sensing applications presented in this review cover a broad range, including strain, temperature, gas and biosensing. The mechanisms and principles governing the sensing capabilities of carbon-based nanocomposites are provided, shedding light on the interactions between analytes and nanocomposite surfaces. A critical analysis of current challenges and prospects is also presented, outlining potential avenues for further research and innovation. Finally, this review aims to serve as a valuable resource for researchers interested in carbon-based nanocomposites and their evolving role in advancing sensing technologies.